THE EFFECT OF TOTAL PHYSICAL RESPONSE METHOD ON STUDENTS’ VOCABULARY FOR SECOND GRADERS OF MTs TPI SAWIT SEBERANG - Sinta Wulandari; Evi Kurniawati; Kiki Triyana; Edi Suprayetno; Yusrah (English Lecturers and Teachers Association (ELTA), 2023)
ABSTRACT This study used a hybrid methodology that combined quantitative and qualitative techniques. This study aimed to find out whether Total Physical Response (TPR) method significantly affects the students' vocabulary for second graders of MTs TPI Sawit Seberang. There were two classes were chosen as the sample of this study where class VIII B was the experimental group and VIII A was the control group which consists of 25 students in each group. A quasi-experimental design was employed by giving pre-test and post-tests to the two groups (control and experiment) where the treatment using TPR method was given to the experimental group, while the control group was taught by the traditional method. The results of this study showed that the significance score was 0,000 which means < 0.05. It means that Ho was rejected and Ha was accepted. It can be concluded that Total Physical Response (TPR) method significantly affects the students' vocabulary mastery of second graders of MTs TPI Sawit Seberang. The results of observational research also showed that the assessment of this method's benefits in lowering pressure and stress for students. The Data from field notes revealed that students happily engaged in the class activity without experiencing any stress. Keyword: TPR Method, Vocabulary Mastery